EFFECTS OF PLYOMETRIC JUMP TRAINING ON RUNNING ECONOMY IN ENDURANCE RUNNERS: A SYSTEMATIC REVIEW AND META-ANALYSIS (Kinesiology, 2023)
Running economy (RE) has a strong relationship with distance running performance and is defined as the energy demand for a given velocity. Plyometric jump training may improve RE. The present study aimed to assess the effects of plyometric jump training on endurance runners’ running economy and to estimate the effectiveness of program duration, training frequency, total sessions, age, training status and velocity. A literature search was performed using PubMed/MEDLINE, Web of Science, and SCOPUS databases. Subgroup and single training factor analyses of program duration, frequency, total sessions, chronological age, training status, and running velocity were performed. A random-effects model for meta-analyses was used. Eighteen studies were selected for the systematic review and 10 for the meta-analysis. A trivial effect was noted for plyometric jump training on running economy (ES=0.19). However, plyometric jump training combined with resistance training revealed a large effect on running economy (ES=1.34). Greater running economy improvements were noted after training interventions with >15 total sessions (ES=1.00), >7 weeks (ES=0.95) and >2 days/week (ES=0.89). The youngest (ES=0.95) and highly trained participants (ES=0.94) with faster velocities (ES=0.95) obtained better results. Our findings highlight the effect of plyometric jump training that may improve running economy, particularly in combination with resistance training, after longer-term interventions (i.e., >15 total sessions, >7 weeks), with greater frequency, and among younger and more highly trained runners, especially during running at higher competitive velocities.Key words: running performance, human biomechanics, stretch-shortening cycle, high-intensity interval training, resistance training